Peran Guru Dan Diskursus Moderasi Beragama - Apetatu, Moh. Farhan (MAN Alor, 2024)
Religious moderation is the answer to all issues of conflict based on differences in ethnicity, religion and belief. Moderation is very important to learn in order to create a lasting peace. Moderation habituation must start from an early age, starting from school starting with children, starting from school, of course with the help and guidance of educators or teachers. The purpose of this study was to find out how the role of teachers in instilling the values ​​of religious moderation. This research uses library study method. The conclusion obtained from this scientific paper is that the role of the teacher attached to his duties and functions can be realized in an effort to develop a culture of moderation in students. The teacher as a supervisor is able to provide space to guide students in the learning process by interpreting the values ​​of moderation. The teacher as a model and example can be an example for students, especially in finding a person who applies a moderate life. The teacher becomes a useful facilitator to facilitate students in the learning process and practice which shows the sides of moderation. The role of the teacher is very important for the continuity of moderation, especially for students